2018
DOI: 10.1074/jbc.ra117.001137
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the 5′-flap junction in the active site controls the rate of flap endonuclease-1–catalyzed DNA cleavage

Abstract: Flap endonucleases catalyze cleavage of single-stranded DNA flaps formed during replication, repair, and recombination and are therefore essential for genome processing and stability. Recent crystal structures of DNA-bound human flap endonuclease (hFEN1) offer new insights into how conformational changes in the DNA and hFEN1 may facilitate the reaction mechanism. For example, previous biochemical studies of DNA conformation performed under non-catalytic conditions with Ca have suggested that base unpairing at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 35 publications
(102 reference statements)
4
26
1
Order By: Relevance
“…3 D & 3E) [72] ; this is consistent with findings from bulk cleavage assays [75] , [90] , [91] . Hence, the 5′ flap release is instantaneous [55] , [72] , [91] , the single turnover rate for catalysis ( k STO ) can be determined from the inverse of the average dwell time prior to cleavage ( k STO = 1/Avg τ bending-Flap ). This k STO includes DNA bending, protein ordering for active site assembly, chemistry and 5′ flap release.…”
Section: Monitoring Dna Bending and 5′ Flap Cleavagesupporting
confidence: 85%
See 1 more Smart Citation
“…3 D & 3E) [72] ; this is consistent with findings from bulk cleavage assays [75] , [90] , [91] . Hence, the 5′ flap release is instantaneous [55] , [72] , [91] , the single turnover rate for catalysis ( k STO ) can be determined from the inverse of the average dwell time prior to cleavage ( k STO = 1/Avg τ bending-Flap ). This k STO includes DNA bending, protein ordering for active site assembly, chemistry and 5′ flap release.…”
Section: Monitoring Dna Bending and 5′ Flap Cleavagesupporting
confidence: 85%
“…The probability density plot of the distributions of the dwell time before cleavage ( τ bending-Flap ) of NonEQ and EQ DF-6,1 showed that both substrates are cleaved with similar kinetics ( Fig. 3 D & 3E) [72] ; this is consistent with findings from bulk cleavage assays [75] , [90] , [91] . Hence, the 5′ flap release is instantaneous [55] , [72] , [91] , the single turnover rate for catalysis ( k STO ) can be determined from the inverse of the average dwell time prior to cleavage ( k STO = 1/Avg τ bending-Flap ).…”
Section: Monitoring Dna Bending and 5′ Flap Cleavagesupporting
confidence: 84%
“…However, handing off a bent DNA is not a must for FEN1 activity since FEN1 can actively bend the nick junction in diffusion-limited kinetics 54,55 . Nick translation occurs at rates that are 10-fold faster than nick DNA product release by FEN1 16,[55][56][57] . This suggests that Pol δ and FEN1 must be actively handing off their products during nick translation.…”
Section: Resultsmentioning
confidence: 99%
“…This distorted structure projects the HJ for the second GEN1 monomer to bind before licensing catalysis. DNA-induced fit binding has also been illustrated in FEN1 and Exo1, two members of the 5′ nuclease superfamily to which GEN1 belongs (39,57). Increasing structural evidence also suggests that the proteins undergo conformational changes upon DNA binding, which control active-site assembly in GEN1 (35,36), FEN1 (37,41) and Exo1 (42,43).…”
Section: Discussionmentioning
confidence: 96%
“…In the case of FEN1, the protein uses an induced-fit mechanism where it actively pulls out a nucleotide at the 3′ end of the nick junction to drive protein ordering (39,40). This step locks the protein and the DNA interactions to verify their ability to promote the transition state (39,57,58).…”
Section: Discussionmentioning
confidence: 99%